Pengaruh Konsentrasi Air Kelapa Muda Terhadap Pertumbuhan Setek Tanaman Lada (Piper nigrum L) - Masnenah, Endeh; Hidayatulloh, Ivan; Aisyah, Iis (OrchidAgro, 2024)
The aim of this research was to study the effect of young coconut water concentration on the growth of pepper plant cuttings. The research was carried out in the Legok ringgit village of Padaulun Village, Majalaya District, Bandung Regency at an altitude of 796 meters above sea level, from September to November 2020. The experiment used a Randomized Block Design (RAK), consisted of five treatments with young coconut water concentration, namely A = without young coconut water (control); B = 25% young coconut water concentration; C = 50% young coconut water concentration; D = 75% young coconut water concentration; E = 100% young coconut water concentration, and replicated five times.The experimental results showed that the concentration of young coconut water had an influence on the percentage of live cuttings, number of leaves, root length, number of roots and root volume. A concentration of 75% young coconut water had the best effect on the percentage of live cuttings, number of leaves, root length, number of roots and root volume of pepper cuttings.